Analisis Evapotranspirasi dan Neraca Air Tanaman Jagung (Zea mays L.) menggunakan Cropwat 8.0 - Sillviana Yuan Arista; Dewi Fortuna; Yulfita Farni (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2026)
Cropwat 8.0 is a software that functions to estimate the needs of plant water and irrigation. This device performs its calculations by analyzing data on soil type, climate conditions, and the characteristics of certain plants. This study was designed to analyze evapotranspiration and water balance in corn plants (Zea mays L.). This analysis is important to analyzing evapotranspiration, water balance, and determining the optimal planting pattern of corn (Zea mays L.) in Rengas village, Bandung Muaro Jambi Regency, using the Cropwat 8.0 application. This research was carried out using quantitative methods with several research stages to be carried out. The research results showed that the highest ETo value was in March at 104,97 mm/month, while the lowest ETo was in June at 85,69 mm/month. The average annual ETo was 1136,08 mm/month. The results of the water balance analysis show a water surplus throughout the year, namely from January to December, where the average monthly rainfall in Rengas Village, Bandung, Muaro Jambi Regency for the period 2013-2022 is between 130,4-305,8 mm, exceeding the evapotranspiration value between 2,99-3,86 mm/day, so the availability of water in corn plants is sufficient. The corn planting pattern carried out in Rengas Village, Bandung, Muaro Jambi Regency, planting in May and harvesting in early September is suitable based on simulations using the Cropwat 8.0 application to analyze evapotranspiration and water balance of corn plants (Zea mays L.).